High-performance infrared photodetector based on single-wall carbon nanotube films. (25th March 2023) - Chen, Chao; Zhao, Yi-Ming; Yu, Hai-Long; Jiao, Xin-Yu; Hu, Xian-Gang; Li, Xin; Hou, Peng-Xiang; Liu, Chang; Cheng, Hui-Ming
Abstract: Bolometric photodetectors based on single-wall carbon nanotubes (SWCNTs) have shown advantages of an ultrawide absorption spectrum, high charge carrier mobility, good processability, and high mechanical flexibility. However, their detection performance needs to be improved to meet the requirements of real applications. A flexible infrared photodetector was fabricated based on high quality SWCNT films. The device showed an ultrahigh detectivity up to 1.35 × 10 8 Jones under a bias voltage of 0.2 V, and a short response time of 70 ms in air. In addition, we found that the photocurrent response of the detector was closely related to the structure of the SWCNT network. A negative photocurrent was measured using photodetectors constructed from highly-crystalline SWCNTs owing to dominant phonon scattering transfer, while a positive photocurrent was detected from those fabricated using defect-rich SWCNTs due to dominant electron hopping transfer. Our results shed light on the construction of high-performance SWCNT film-based infrared photodetectors. Graphical abstract: A high negative photocurrent was measured using photodetectors constructed from highly-crystalline SWCNTs (IG /ID ∼177) owing to dominant phonon scattering transfer, while a positive photocurrent was detected from those fabricated using defect-rich SWCNTs (IG /ID ∼31) due to dominant electron hopping transfer. Image 1